Class II major histocompatibility complex molecules of murine dendritic cells: synthesis, sialylation of invariant chain, and antigen processing capacity are down-regulated upon culture. - Kämpgen, E (1991)
Dendritic cells (DCs), such as Langerhans cells (LCs) of the epidermis and the DCs of lymphoid organs such as spleen, are potent antigen presenting cells. DCs express high levels of major histocompatibility complex (MHC) class II molecules, but, partly because of the low numbers of primary DCs in any tissue, there has been no detailed study of the biochemistry of their class II molecules. This information may be needed to help explain recent findings that DCs process native protein antigens when freshly isolated from epidermis and spleen. Processing ceases during culture, yet a strong accessory function for activating resting T cells develops. We studied immunoprecipitates of DC class II and invariant chain (Ii) molecules by two-dimensional gel electrophoresis. We found that (i) freshly isolated LCs synthesize large amounts of class II and Ii polypeptides; (ii) Ii molecules that are known to be involved in antigen processing display an unusually large number of sialic acids in fresh LCs; (iii) with culture, class II and Ii synthesis decreases dramatically and has virtually ceased at 3 days; and (iv) the turnover of class II in pulse/chase experiments is slow, being undetectable over a 12- to 32-hr culture period, whereas the turnover of Ii is rapid. We conclude that MHC class II molecules of DCs do not seem to be qualitatively unique. However, the regulation of class II and Ii expression is distinctive in that biosynthesis proceeds vigorously for a short period of time and the newly synthesized class II remains stably on the cell surface, whereas Ii turns over rapidly. This may enable DCs to process and retain antigens in the peripheral tissues such as skin and migrate to the lymphoid organs to activate T cells there.